2001
DOI: 10.1103/physrevlett.86.1143
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Linewidth of an Atom Laser by Feedback

Abstract: A continuous atom laser will almost certainly have a linewidth dominated by the effect of the atomic interaction energy, which turns fluctuations in the condensate atom number into fluctuations in the condensate frequency. These correlated fluctuations mean that information about the atom number could be used to reduce the frequency fluctuations, by controlling a spatially uniform potential. We show that feedback based on a physically reasonable quantum non-demolition measurement of the atom number of the cond… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 25 publications
0
46
0
Order By: Relevance
“…(3.8), except at the boundary between the regimes. This is illustrated by the figure in our previous paper [20], and also the extended version in this paper, Fig. 2 appearing in Sec.…”
Section: Analytical Calculation Of Linewidthmentioning
confidence: 53%
See 1 more Smart Citation
“…(3.8), except at the boundary between the regimes. This is illustrated by the figure in our previous paper [20], and also the extended version in this paper, Fig. 2 appearing in Sec.…”
Section: Analytical Calculation Of Linewidthmentioning
confidence: 53%
“…Collisional interactions therefore lead to a significant decrease in the atom-laser coherence time, and a corresponding increase in the linewidth, especially in the case of BECs formed by evaporative cooling. However, we have previously shown that a continuous, quantum nondemolition (QND) feedback scheme can effectively cancel the linewidth broadening due to such collisions [20].…”
Section: Introductionmentioning
confidence: 99%
“…This effect is not dependent on the output coupling, but could possibly be controlled by a highly mode selective pumping mechanism. This result is important in the design of continuously pumped atom lasers because the Kerr-like phase diffusion will scale with the interactions, and will induce a fundamental limit to the linewidth of the atom laser beam [14]. Because of the opposite scaling of the semiclassical and the quantum noise, if an atom laser can be operated in a stable regime then we expect it to have a minimum linewidth at an optimum scattering length.…”
mentioning
confidence: 99%
“…It is also extremely difficult to include the effects of the atomic interactions in these models. Atom laser linewidths will be limited by these interactions due to Kerr-like dephasing of the lasing mode [14], as well as by thermal effects [15].…”
mentioning
confidence: 99%
“…In this paper we present a measurement scheme * sandeep.goyal@ucalgary.ca that would appear to violate this idea; i.e., we appear to distinguish between two preparation methods. This measurement scheme uses unsharp measurements that are also known as positive operator valued measurements (POVMs) [7][8][9][10]. We present a special class of POVMs that can cause the recurrence of the original state of the quantum system upon repeated measurements.…”
Section: Introductionmentioning
confidence: 99%